Association of ApoE Genotypes and Recovery From Intracerebral Hemorrhage in Very Low Birth Weight Infants. Issue 2 (February 2022) - Humberg, Alexander; Dzietko, Mark; Schulz, Sören; Felderhoff-Müser, Ursula; Hüning, Britta; Stein, Anja; Fortmann, Mats I.; Marissen, Janina; Rausch, Tanja K.; Herting, Egbert; Härtel, Christoph; Göpel, Wolfgang
Abstract : Background and Purpose: Associations of APOE genotypes with intracerebral hemorrhage (ICH) in preterm infants were previously described. In adults, APOE-ε4 genotype has been proposed as susceptibility factor for impaired recovery after cerebral insult. We here aim to determine APOE genotype-specific neurological consequences of neonatal ICH at school age. Methods: In this multicenter observational cohort study, very low birth weight (<1500 g, <32 weeks gestational age) children were studied for cerebral palsy (CP) after ultrasound diagnosed ICH stratified by APOE genotype. Follow-up examination was done at the age of 5 to 6 years. Study personnel were blinded for perinatal information and complications. Participants were born between January 1, 2009 and December 31, 2013 and enrolled in the German Neonatal Network. Of 8022 infants primarily enrolled, 2467 children were invited for follow-up between January 1, 2014 and December 31, 2019. Univariate analyses and multivariate logistic regression models were used to assess the impact of APOE genotype (APOE-ε2, APOE-ε3, APOE-ε4) on CP after ICH. Results: Two thousand two hundred fifteen children participated at follow-up, including 363 children with ultrasound diagnosed neonatal ICH. In univariate analyses of children with a history of ICH, APOE-ε3 carriers had lower frequencies of CP (n=33/250; 13.2 [95% CI, 9.4%–17.8%]), as compared to APOE-ε2 (n=15/63; 23.8 [14.6%–35.3%], P =0.037) and –ε4 carriers (n=31/107; 29.0 [21.0%–38.0%], P <0.001), respectively. Regression models revealed an association of APOE-ε4 genotype and CP development (odds ratio, 2.77 [1.44–5.32], P =0.002) after ICH. Notably, at low-grade ICH (grade I) APOE-ε4 expression resulted in an increased rate of CP (n=6/39; 15.4 [6.7–29.0]) in comparison to APOE-ε3 (n=2/105; 1.9 [0.4%–6.0%], P =0.002). Conclusions: APOE-ε4 carriers have an increased risk for long-term motor deficits after ICH. We assume an effect even after low-grade neonatal ICH, but more data are needed to clarify this issue. Abstract : Supplemental Digital Content is available in the text.